Yearly dynamics of the content and composition of total lipid and lipid classes in the hydrocoral \(Millepora platyphylla\) from coastal water of Nha Trang, Khanh Hoa, Vietnam - Dang Thi, Phuong Ly; Nguyen, Ba Kien; Dang Thi, Minh Tuyet; Trinh Thi, Thu Huong; Pham Quoc Long, Pham Quoc Long; Borisovich, Andrey Imbs (Vietnam Journal of Marine Science and Technology, 2022)
The coral Millepora platyphylla was collected for 12 consecutive months in the Nha Trang, Khanh Hoa, coastal areas to study their lipid content and composition. The total lipid content (dry weight) ranged from 0.26–0.63%. The total content tends to increase in the summertime and decrease in the wintertime and there is a correlation with the ambient sampling temperature. The fatty acid class (FFA) accounts for less than 2% of the total lipid. The sterol class (ST) ranged from 6.81–9.86%, polar lipid (PL): 11.07–18.92%, monoalkyldiacylalycerol (MADAG): 18.41–22.78%, wax layer (W): 18.65–25.0%, trialkyldiacylalycerol (TAG) accounted for the largest proportion in total lipid, ranged from 27.58–35.32%. The seasonal variation is significant: the content of FFA, ST, PL decrease during summertime and increase in wintertime, and in contrast to the class of MADAG, W, and TAG. The lipid reverse class (TAG, MADAG, W) is more stable than structural lipid classes (PL, ST). The decrease in W between samples collected in September-October, the TAG concentration between the sample in October-November, the high distribution of the PL concentration in December might closely related to the changing habitat, such as seasonal water temperature and solar radiation, as well as the maturation and reproduction of Millepora platyphylla.